Perempuan dan Terorisme: Studi Literatur di Indonesia - Achievinna Mirza Senathalia; Nurjanah Nurjanah (Jurnal Kawakib, 2022)
The focus of this article discusses the development of literature on the theme of women and terrorism in Indonesia. Primary data in the form of scientific articles obtained from online sources such as online journals were analyzed using qualitative descriptive methods. The findings of this article show that there are many studies and articles published with various focuses or topics related to the themes of women and terrorism. Studies related to women and terrorism in Indonesia can be classified covering topics of women's involvement, women's roles, women's absence, media, and gender. Therefore, this article confirms that the study of women and terrorism is growing and diversified along with the increasing phenomenon of women's terrorism